2021
DOI: 10.3390/ma14071636
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of High-Temperature Superconductor Bulks for Electrical Machine Application

Abstract: High-temperature superconducting (HTS) bulks can be used in electrical applications. Experimental characterization of large-size HTS bulks is a tricky issue. The relevant parameters for their application were directly measured in this study. This paper has three main aims. Firstly, features of YBaCuO bulks are presented. Secondly, an electrical motor application is developed using magnetic field shielding and trapping. Thirdly, the HTS bulks are characterized. Several classical methods were used, which are mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Later on, scientists defined the critical temperature (the transition temperature from superconducting state to normal state) as 30 K, to distinguish the low-temperature superconductor (LTS) and hightemperature superconductor (HTS) [2]. The practical superconductors for engineering can be made in the forms of bulks or wires (tapes) [3,4]. For commercial superconducting wires, based on different manufacture processes, there are two generations of superconductors: 1st generation (1G) superconducting wires use the powder-in-tube process, such as the superconducting wires use the coated conductor method to deposit the rare-earth-bariumcopper-oxide (REBa 2 Cu 3 O 7 , RE: rare earth [5]) on flexible metal tapes coated by multiple buffering layers [6].…”
Section: Introductionmentioning
confidence: 99%
“…Later on, scientists defined the critical temperature (the transition temperature from superconducting state to normal state) as 30 K, to distinguish the low-temperature superconductor (LTS) and hightemperature superconductor (HTS) [2]. The practical superconductors for engineering can be made in the forms of bulks or wires (tapes) [3,4]. For commercial superconducting wires, based on different manufacture processes, there are two generations of superconductors: 1st generation (1G) superconducting wires use the powder-in-tube process, such as the superconducting wires use the coated conductor method to deposit the rare-earth-bariumcopper-oxide (REBa 2 Cu 3 O 7 , RE: rare earth [5]) on flexible metal tapes coated by multiple buffering layers [6].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, superconductivity is a phenomenon first understood, approaching close to 4 degrees Celsius of absolute temperature in Kelvin [16]. Twenty-two years after this work, German researchers Walther Meissner and Robert Ochsenfeld, while studying the behavior of matter at extremely cold temperatures, found that a superconducting material affects the magnetic field [17][18][19]. As in the working principle of the electric generator, a magnet moved in a conductor induces an electric current.…”
Section: Introductionmentioning
confidence: 99%
“…The development of High-Temperature Superconductors (HTSs) such as the cuprate family with the REBaCuO superconductors (Rare Earth elements (RE)), the Iron-Based Superconductors (IBS) with the Pnitide and Chalcogen families and the MgB 2 compound allow a quick evolution of superconducting devices for many applications. Among them, lead by ecological, economical, and practical needs, the electrical machines associated with superconducting materials such as electromagnet [1], permanent magnets [2][3][4][5], or windings [6,7] look increasingly more attractive for future transports such as electrical ships [8], aircraft [9][10][11], and levitation trains [12] for the high specific power potential of HTS machines. Indeed, for the aviation sector in particular, the growing need for electrical power on board requires the development of electrical machines with a target power-to-weight ratio of 20 kW/kg for MW class machines [4,13,14].…”
Section: Introductionmentioning
confidence: 99%